Gas purification using pure ionic liquids and ionic liquid - polymer mixtures as absorbents - Garbis, Panagiota-Katerina (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Χημικών Μηχανικών. Τομέας Ανάλυσης, Σχεδιασμού και Ανάπτυξης Διεργασιών και Συστημάτων (ΙΙ), 2016)
The interest in ionic liquids (melting point below 100°C; IL) and their potential applications are still rising in academia as well as industry due to the variety of their chemical and physical properties. In separation processes, evaporation losses and product contaminations can be avoided because of their very low vapor pressure. A number of ionic liquids have hygroscopic character, so they can absorb a certain extent of water. This property can be an advantage for gas and fluid drying. Gas drying is an important separation process for drying of natural gas in order to avoid corrosion and hydrate formation in the pipelines. In the industry, the absorptive gas scrubbing with glycols (especially with triethylene glycol; TEG) as absorbent is well established. The absorption of hydrogen sulfide is also of great importance in the gas industry. The toxicity and corrosive properties of H2S dictate stringent control of its release into the environment and contact of aqueous solutions of H2S with iron and steel as tanks, piping, valves and pumps. The most common way for the removal of acidic components from gas streams are amine solutions. In contrast to various studies on the absorption of CO2 and SO2 in ILs, the number of publications on absorption of water as well as hydrogen sulfide is still low. ILs could be alternative absorbents for water and hydrogen sulfide absorption too. At the beginning of the 21. Century, ionic liquids were immobilized on porous supports in or-der to combine e.g. the advantages of both the homogeneous and heterogeneous catalysis. Other researchers tried to combine both the unique properties of polymers and ILs. This leads to supported membranes and the so-called “ionogels”. Ionic liquids confined in gel matrices make them suitable in various applications e.g. stable electrolytes in dye-sensitized solar cells, secondary batteries, electrochromic displays, electrolytic membranes and perhaps even for gas separation processes in a kind of “fixed bed absorber”. The present work is divided in two main parts. In the first part the immobilization of the ionic liquids in a polymer matrix and the evaluation, if these hybrid materials are suitable for gas dehydration was investigated. The hygroscopic ionic liquid [EMIM][MeSO3] was immobilized into the three polymers, the agar agar Kobe I and two types of poly(vinyl alcohol) (PVOH) Mowiol 56-98 and Mowiol 40-88. The occurred fouling due to the high amount of water in the agar agar-[EMIM][MeSO3] ionogels was the reason why the PVOH-[EMIM][MeSO3] ionogels were chosen for the gas dehydration. First the main components of the ionic liquid – polymer mixtures were characterized. The thermal decomposition of the [EMIM][MeSO3] was calculat-ed with a ‘’model free’’ method, the isoconversional method (Ea = 137 kJ mol-1, k0 = 6.2 ·108 s-1) and compared with literature data. The calculation of the kinetics of thermal decomposition using the isoconversional method took considerable time without having any advantage com-pared to the TGA-method established at the Chair of Chemical Engineering of University of Bayreuth. At next the thermal decomposition of the two types of PVOH (Mowiol 56-98, Mowiol 40-88) was also determined with the TGA method (Ea = 175 kJ mol-1, k0 = 7.89 1013 s-1). Furthermore the density and viscosity of the prepared IL - polymer mixtures were measured. Based on the results the IL - polymer mixtures with about 10 wt% PVOH in [EMIM][MeSO3] were chosen for the gas dehydration measurements. Therefor a dehydration plant was build up. The experiment was accomplished at an absorbent temperature of 42 °C and three differ-ent dew points of the feed gases. Comparison of the activity coefficients of water in the iono-gels compared with the activity coefficients of water in the pure ionic liquid show no measur-able deviation from each other. This means that the polymer matrix doesn’t influence the absorption capacity of the ionic liquid in greater extend. In the second part of this study, the absorption of the hydrogen sulfide was accomplished us-ing the [EMIM][MeSO3] as an absorbent. The measurements showed that the ionic liquid [EM-IM][MeSO3] is suitable for the purification of gas from its hydrogen sulfide component. For the absorption temperature of 22 °C, the Henry coefficient of H2S in the [EMIM][MeSO3] is 3 924 mbar and by a factor of about 1.5 lower compared to the N-methylpyrrolidone at 20°C. The Henry coefficient of the H2S in [EMIM][MeSO3] for a temperature of 32 °C is 5 041 mbar and by a factor of 5,7 lower compared to the ionic liquid [hemim][BF4] at a temperature of 30 °C. In conclusion, the present work shows that the ionic liquid [EMIM][MeSO3] can be immobi-lized into the polymer poly(vinyl alcohol) without losing its absorption capacity. On the basis of the results, the main idea to get a kind of “fixed bed absorber” seems to be possible since the IL - polymer mixtures keep the absorption capacity of the ionic liquid. Further studies con-cerning the ternary mixtures H2O - IL - polymer should be conducted in order to get more in-formation about the mechanism of gelation, rheological behavior, miscibility gaps and infor-mations about the mass transfer in such a gel layer. The investigation on separating the hydrogen sulfide (H2S) with the ionic liquid [EM-IM][MeSO3] from a gas stream showed that the [EMIM][MeSO3] has a good absorption capacity. It is already proven that the [EMIM][MeSO3] is an alternative drying agent to the absorbent TEG commonly used for industrial gas drying. In the ideal case, both gases would be absorbed simultaneously. Therefor it should be furthermore investigated if the [EMIM][MeSO3] can also separate H2S from natural gas in presence. Both the experimental part and the written composition of this work were conducted during a stay at the Chair of Chemical Engineering at the University of Bayreuth, which was funded by the Erasmus Exchange Programme.